Students' experience of being seen by their physical education teachers and associated factors - Andresen, Fredrik; Torvik, Eli; Lagestad, Pål (Frontiers in Sports and Active Living, 2023)
Background: The experience of being seen by the physical education (PE) teachers is an important pedagogical term at schoolin school settings, and is – a term who that is closely related to the theory of recognition pedagogy and self-determination theory. However, very few studies have been conducted concerning this term, and the extant research has typically been based on small sample sizes, and thus is - and so are unlikely to be extrapolated to other contexts, such as. recognition pedagogy. Purpose: The aim of the study was to examine the extent to which students experience being seen by their PE teacher in PEs, which factors constitutes the phenomenon of being seen as a pedagogical term, and how these factors correlate with students’ experience of being seen by their PE teachers. Method: A questionnaire was developed on the basis of theory and previous research, and data form from 412 students were collected. A pPrincipal component analysis was conducted to examine the dimensionality of the questions and which factors could be associated with "being seen". From out of this, indexes were subsequently created for each factor. The association between these factors and the experience of being seen was studied determined using Spearman's correlation test. Results: The results showed that 76.2% of the students reported being seen by the teacher in PE, while 7.8% reported not being seen, and 16.1% of the students neither disagreed nor agreed to being seenE. The factor analysis indicated that “being seen” may be related to students’ experience of the following: being able to display their skills, ; the teacher’s’s caring behavior, ; feedback from the teacher, the dialogue with the teacher; and evaluation and goals. The correlation analysis shows showed that these five factors correlated significantly at a medium level with the students' experience of being seen by their PE teacher in PE. Conclusion: The results point toward the importance of PE teachers giving their students opportunities to display their skills, giving providing the students with feedback through good dialogue, showing them that their teachers cares, and involving students in evaluation and establishing goals in PE.